Proceedings of the 8th ACM SIGSAC Symposium on Information, Computer and Communications Security 2013
DOI: 10.1145/2484313.2484347
|View full text |Cite
|
Sign up to set email alerts
|

Boolean symmetric searchable encryption

Abstract: In this article we tackle the issue of searchable encryption with a generalized query model. Departing from many previous works that focused on queries consisting of a single keyword, we consider the the case of queries consisting of arbitrary boolean expressions on keywords, that is to say conjunctions and disjunctions of keywords and their complement. Our construction of boolean symmetric searchable encryption BSSE is mainly based on the orthogonalization of the keyword field according to the Gram-Schmidt pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The scheme requires a linear search time and provides some false positive results. Many other schemes have been proposed to improve the efficiency of keyword search by implementing an inverted searchable index [4,6,13,23]. Chang et al [13] showed an index construction that enables keyword search without false positive results.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The scheme requires a linear search time and provides some false positive results. Many other schemes have been proposed to improve the efficiency of keyword search by implementing an inverted searchable index [4,6,13,23]. Chang et al [13] showed an index construction that enables keyword search without false positive results.…”
Section: Related Workmentioning
confidence: 99%
“…The score is calculated between the search query (that contains multiple keywords) and the set of encrypted documents. Moataz et al [4] developed the Boolean Symmetric Searchable Encryption (BSSE) scheme. The scheme is based on the orthogonalization of the keywords according to the Gram-Schmidt process.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable amount of research has been done towards this problem that resulted in very efficient and expressive schemes [1][2][3][4][5][6]. However, in searchable encryption schemes, the data to be joined must be encrypted under the same key that has been shared among the owners.…”
Section: Related Workmentioning
confidence: 99%